Sunscreen Use on the Dorsal Hands at the Beach - Donald B. Warren; Ryan R. Riahi; Jason B. Hobbs; Richard F. Wagner (Journal of Skin Cancer)
Background. Since skin of the dorsal hands is a known site for the development of cutaneous squamous cell carcinoma, an epidemiologic investigation was needed to determine if beachgoers apply sunscreen to the dorsal aspect of their hands as frequently as they apply it to other skin sites. Aim. The aim of the current study was to compare the use of sunscreen on the dorsal hands to other areas of the body during subtropical late spring and summer sunlight exposure at the beach. Materials and Methods. A cross-sectional survey from a convenience sample of beachgoers was designed to evaluate respondent understanding and protective measures concerning skin cancer on the dorsal hands in an environment with high natural UVR exposure. Results. A total of 214 surveys were completed and analyzed. Less than half of subjects (105, 49%) applied sunscreen to their dorsal hands. Women applied sunscreen to the dorsal hands more than men (55% women versus 40% men, ). Higher Fitzpatrick Skin Type respondents were less likely to protect their dorsal hands from ultraviolet radiation (). Conclusions. More public education focused on dorsal hand protection from ultraviolet radiation damage is necessary to reduce the risk for squamous cell carcinomas of the hands.